INOVASI PEMBELAJARAN AGAMA DALAM ERA DISRUPSI - Oktavianus Jeffrey Budiarto (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2022)
Advances in information and communication technology have brought the world of education into a new era. Every student, especially in urban areas, has a gadget. They can easily and quickly navigate the virtual world, access information, socialize or have recreation with online games. They are comfortable spending time there. The audio visual design is so very tempting and catches their attention. Teachers and books are slowly getting overlooked. They prefer to look down at the screen and dissolve in virtual reality. This is the phenomenon of disruption that is hitting our world of education. The relationship between teachers and students is disturbed by the existence of gadgets with all the sophistication it offers. The era of disruption is an era of desacralization. Schools and teachers are no longer primary sources of knowledge. Like the jargon of a cellphone advertisement, now the world is in everyone's hands. The role of the teacher becomes relative in the search for